Diabetes Mellitus and Hypertension are Risk Factor for Endometrial Cancer - Wijaya, Chresni F. (Indonesian Journal of Obstetrics and Gynecology, 2012)
Objective: To find out whether diabetes mellitus and/or hypertension is associated with endometrial cancer and could increase the staging of the cancer. Method: This was an analytic retrospective descriptive study with cross sectional design. Data were taken from the medical record of patients diagnosed as having endometrial cancer in Obstetrics and Gynecology Department of Dr. Hasan Sadikin Hospital from 1st January 2007 - 31st December 2011 and analyzed descriptively. Result: There were 125 cases of endometrial cancer. Prevalence was 2.56 %. The incidence increased in age > 40 y/o (92 %) and had diabetes mellitus and/or hypertension (66.4 %). Conclusion: Diabetes mellitus and/or hypertension were associated with risk factors of endometrial cancer but not proven to increase the staging of the cancer. [Indones J Obstet Gynecol 2012; 36-3: 140-3] Keywords: diabetes mellitus, endometrial cancer, hypertension